Low-frequency conductivity of a two-dimensional Wigner solid coupled to surface excitations of liquid helium - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The line-shape and broadening of coupled phonon-ripplon resonances of Wigner-solid conductivity are studied using the memory function formalism. The analytic properties of the memory function permit coordinating the approximations of the secular equation for the coupled phonon-ripplon modes and the line-broadening of these resonances. Special attention is paid to the description of the strong-coupling regime realized for surface electrons on superfluid helium. For this case it is shown that the line-broadening is much smaller than and the line-shape is different from those found previously using the weak-coupling theory. Different theoretical approaches are compared with available experimental data.